Riboflavin producing lactic acid bacteria as a biotechnological strategy to obtain bio-enriched soymilk - Juarez del Valle, Marianela (2014)
Riboflavin (vitamin B2) plays an important role in cellular metabolism participating in numerous oxidation–reduction reactions and energy usage. In this work, lactic acid bacteria that can produce vitamin B2 in soymilk were identified from 179 strains tested that were previously isolated from a wide range of food products. Only 42 strains were able to grow in a commercial riboflavin-free medium after which the concentration of this vitamin was determined by HPLC. Five of these strains were pre-selected for their capacity to produce elevated concentrations of riboflavin. Thesewere then inoculated in soymilk to evaluate their capacity to growin this food matrix and increase its lowriboflavin concentrations. Only the strain Lactobacillus plantarumCRL 725 was able to significantly increase the initial concentration of riboflavin in soy milk from 309 ± 9 ng/mL to 700 ± 20 ng/mL after 12 h of incubation at 37 °C. Roseoflavin resistant variants of this strain were obtained and evaluated in soymilk. One of the variant strains increased 6 times (1860 ± 20 ng/mL) the initial riboflavin levels of soy milk. Roseoflavin-resistant strains capable of synthesizing riboflavin in soymilk constitute an interesting and economically feasible biotechnology strategy that could be easily adapted by the food industry to develop novel vitamin-bioenriched functional foods with enhanced consumer appeal.